The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/1749-4877.12292
|View full text |Cite
|
Sign up to set email alerts
|

Seed loss before seed predation: experimental evidence of the negative effects of leaf feeding insects on acorn production

Abstract: Insect herbivory decreases plant fitness by constraining plant growth, survival and reproductive output. Most studies on the effects of herbivory in trees rely on correlational inter-individual comparisons and could, thus, be affected by confounding factors linked to both herbivory and plant performance. Using the Mediterranean Holm oak (Quercus ilex) as a study model, we followed an experimental approach in which leaf-feeding insects (mainly Lepidoptera caterpillars) were excluded from some shoots in all stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 72 publications
2
13
0
1
Order By: Relevance
“…In support of this hypothesis, in one past study, Quercus lobata individuals with earlier budburst suffered more leaf damage, which reduced their seed production (Pearse et al, 2015a). Past experiments in our study system indicated that insect herbivory can decrease Q. ilex seed set by half (Canelo et al, 2018). Early trees gain the advantage of reduced pollen limitation, but may suffer reduced seed set due to other factors, such as herbivory.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In support of this hypothesis, in one past study, Quercus lobata individuals with earlier budburst suffered more leaf damage, which reduced their seed production (Pearse et al, 2015a). Past experiments in our study system indicated that insect herbivory can decrease Q. ilex seed set by half (Canelo et al, 2018). Early trees gain the advantage of reduced pollen limitation, but may suffer reduced seed set due to other factors, such as herbivory.…”
Section: Discussionsupporting
confidence: 79%
“…Past experiments in our study system indicated that insect herbivory can decrease Q . ilex seed set by half (Canelo et al ., 2018). Early trees gain the advantage of reduced pollen limitation, but may suffer reduced seed set due to other factors, such as herbivory.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the strength of this scatterhoarder-tree mutualism is strongest for red oaks (Q. rubra), weakest for white oaks (Q. alba) and intermediate for chestnut oak (Castanea dentata) and hybrid chestnut (C. dentata x Castanea mollissima). Canelo et al (2018) employ a careful experimental approach to quantify the effects of herbivory by a leaf-feeding insect on the Mediterranean Holm oak's (Q. ilex) physiological responses in individual shoots that ultimately results in a drop in acorn production. Unlike other correlational studies, this study demonstrated the causal physiological links between herbivory and reproductive loss.…”
Section: Editorialmentioning
confidence: 99%
“…Most defoliation and herbivore exclusion experiments on temperate forest trees and fruit trees have shown a negative effect of defoliation on fruit set (Mehouachi et al 1995;Obeso 1998;Iglesias et al 2003;Frioni et al 2018) and on fruit size (Obeso 1998;Hoch 2005;Matsumoto et al 2017). In oaks, most studies concerned natural herbivory and showed also negative impact on fruit set and total fruit production (Crawley 1985;May and Killingbeck 1995;Hochwender et al 2003;Pearse et al 2015;Nakajima 2015;Canelo et al 2018). However, other studies have found no effect of herbivory on fruit set, fruit size or yield in other species (Obeso and Grubb 1993;Mehouachi et al 1995;Tamura and Hiura 1998;Ezzahouani and Williams 2003;Bañuelos and Obeso 2005;Frioni et al 2018;Pasqualotto et al 2019).…”
Section: Introductionmentioning
confidence: 99%